A Brief Overview on Antioxidant Activity Determination of Silver Nanoparticles - Zdenka Bedlovičová; Imrich Strapáč; Matej Baláž; Aneta Salayová (Molecules, 2020)
Our objective in this review article is to find out relevant information about methods of determination of antioxidant activity of silver nanoparticles. There are many studies dealing with mentioned problem and herein we summarize the knowledge about methods evaluating the antioxidant activity of silver nanoparticles reported so far. Many authors declare better antioxidant activity of silver nanoparticles compared to the extract used for synthesis of them. In this review, we focused on methods of antioxidant activity determination in detail to find out novel and perspective techniques to solve the general problems associated with the determination of antioxidant activity of silver nanoparticles.